Construction of Liapunov functionals for linear Volterra integrodifferential equations and stability of delay systems - Bo Zhang (Electronic Journal of Qualitative Theory of Differential Equations, 2000)
Inspired by the construction of a new Liapunov functional for linear Volterra integrodifferential equations, we prove some general stability theorems for functional differential equations with infinite delay and weaken the usual requirement for positive definiteness of Liapunov functionals involved in stability theory.